2004
DOI: 10.1093/jn/134.6.1459
|View full text |Cite
|
Sign up to set email alerts
|

Avenanthramides and Phenolic Acids from Oats Are Bioavailable and Act Synergistically with Vitamin C to Enhance Hamster and Human LDL Resistance to Oxidation

Abstract: The intake of phenolic acids and related polyphenolic compounds has been inversely associated with the risk of heart disease, but limited information is available about their bioavailability or mechanisms of action. Polyphenolics, principally avenanthramides, and simple phenolic acids in oat bran phenol-rich powder were dissolved in HCl:H(2)O:methanol (1:19:80) and characterized by HPLC with electrochemical detection. The bioavailability of these oat phenolics was examined in BioF1B hamsters. Hamsters were gav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
131
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(139 citation statements)
references
References 50 publications
3
131
0
2
Order By: Relevance
“…Oat phenolics may serve as potent antioxidants by scavenging reactive oxygen and nitrogen species and/or by chelating transition minerals (Chen et al 2004). AVAs are important phenolic compounds found in oats.…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Oat phenolics may serve as potent antioxidants by scavenging reactive oxygen and nitrogen species and/or by chelating transition minerals (Chen et al 2004). AVAs are important phenolic compounds found in oats.…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…Both animal studies and human clinical trials confirmed that oats antioxidants have the potential of reducing cardiovascular risks by lowering serum cholesterol, inhibiting LDL cholesterol oxidation and peroxidation (Cook & Samman 1996;Ji et al 2003;Inglett & Chen 2012). Therefore, it is emphasised that the consumption of oats and oats products is extremely important to reduce the risk of cardiovascular disease (Bazzano et al 2003;Chen et al 2004Chen et al , 2007Singh et al 2013). Another study has indicated that the consumption of oats and oats bran may reduce the risk of colon cancer not only because of their high fiber contents but also due to AVAs (Guo et al 2010).…”
Section: Effects Of Avenanthramides On Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary fiber is present in large quantities and this is rich in fructo-oligosaccharides, which are reportedly effective at stimulating the growth of Bifidobacteria and Lactobacilli in the human intestine (K. D. Kaur, Jha, Sabikhi, & Singh, 2011). Besides this prebiotic effect, their phenolic compounds have also been reported to possess gastroprotective properties, in addition to their antioxidant, cholesterol-lowering, anti-atherogenic, anti-carcinogenic and anti-inflammatory effects (C. Chen et al, 2004;Dykes & Rooney, 2006;Prior & Gu, 2005). Indeed, epidemiological studies have shown an association between increased wholegrain consumption and reduced risks of various types of chronic diseases, such as CVD, obesity, DM-2 and some cancers (Chan, Wang, & Holly, 2007;de Munter, Hu, Spiegelman, Franz, & van Dam, 2007;Esmaillzadeh, Mirmiran, & Azizi, 2005;Larsson, Giovannucci, Bergkvist, & Wolk, 2005;Mellen, Walsh, & Herrington, 2008;Murtaugh, Jacobs, Jacob, Steffen, & Marquart, 2003;Schatzkin, Park, Leitzmann, Hollenbeck, & Cross, 2008;van de Vijver, van den Bosch, van den Brandt, & Goldbohm, 2009).…”
Section: Cereal Grains and Their Milksmentioning
confidence: 99%
“…Avenanthramides are amides of cinnamoylanthranilic acids and are found exclusively in oats. They have anti-inflammatory, anti-atherogenic and antioxidant properties (Emmons et al 1999;Chen et al 2004). Alkyl resorcinol produced by various plants, bacteria and fungi are bioactive compounds possessing beneficial activities for human health such as anticancerous activity (Kozubek and Tyman 1999;Ross et al 2004).…”
Section: -746mentioning
confidence: 99%